RECENT ADVANCEMENTS IN DEFECTED GROUND STRUCTURE-BASED NEAR-FIELD WIRELESS POWER TRANSFER SYSTEMS - Dautov, Kassen; Hashmi, Mohammad; Nauryzbayev, Galymzhan; Nasimuddin, Nasimuddin (Institute of Electrical and Electronics Engineers, 2020)
The defected ground structure (DGS) technique enables miniaturization of the resonator which leads to the development of the compact near-field wireless power transfer (WPT) systems. In general, numerous challenges are inherent in the design of the DGS-based WPT systems and, hence, appropriate trade-offs for achieving optimal performance are required. Furthermore, the design advancements have led to the development of the DGS-based multi-band WPT systems to fulfill the needs of simultaneous data and power transfer. The innovations in the DGS-based WPT systems have also resulted in the definition of more commonly used figures-of-merit for the benchmarking of various performance metrics. The literature is replete with the design schemes to address one or more associated design challenges and successful WPT system realizations with enhanced performance. With this in mind, this paper touches upon the DGS-based WPTs developments and presents a concise report on the current state-of-the-art and future directions.
Keywords: Coupling; defected ground structure (DGS); multi-band; resonator; Q factor; single-band; wireless power transfer (WPT); Research Subject Categories::TECHNOLOGY